Copy number variation in association studies of human disease - McCarroll, Steven (Henry Stewart Talks, 2009)
Why study CNV in human disease?, Population genetics of human CNV, Low copy sequences, Medium-to-large CNVs, Inheritance vs. de novo mutation, Common CNV regions, Rare and common variants, Most common CNPs are in LD with SNPs, Haplotype sharing, GWAS, Association frameworks for analyzing CNVs, Data quality in CNV studies, Interpreting CNV-disease association findings